Primary aorto enteric fistula as a cause of massive upper gastro-intestinal bleed-a very rare case presentation - Mudadla, Rohith; Kamal, Harshit; Purushothaman, Govind; Satyanesan, Jeswanth (International Surgery Journal, 2022)
Primary aortoenteric fistula (PAEF) is spontaneous development of communication between the native aorta and anywhere within the gastrointestinal tract. It is extremely rare and fatal condition which usually presents as a painless upper gastrointestinal bleed. This condition is often overlooked because of it's rarity and low index of suspicion by physicians despite the availability of a wide range of diagnostic tools. Computed tomography angiography (CTA) is the most common investigation done to diagnosis PAEF. This paper reports a case of 49 years old female with massive upper gastrointestinal (GI) bleeding. A PAEF was diagnosed by CTA which called for an emergency laparotomy with surgical repair of the fistula with a synthetic vascular bypass graft. The patient recovered well.